Functional traits and adaptive capacity of European forests to climate change - Bussotti, Filippo; Pollastrini, Martina; Holland, Vera; Brüggemann, Wolfgang (Environmental and Experimental Botany, 2014)
Increasing temperatures and drought risks through climate change are expected to have several consequences for European forests. Adaptive strategies may include: (i) persistence of the current forest types, thanks to the acclimatization to local conditions and to phenotypic plasticity of the populations; (ii) evolution, or local adaptation, i.e., change in genotype (frequencies) within the same species due to environmental pressure. It is favored by large within population diversity and (when possible) gene flow among populations; (iii) migration and substitution of species; and (iv) extinction of populations with low ecological plasticity, especially at the edges of their distribution or in the case of isolated (relict) populations. Because of the economic and ecological relevance of forests, it is of fundamental importance to apply appropriate forest management to make forests able to cope with the new environmental conditions. This may include changes in the composition and structure of forest stands, selection of adapted provenances of the most important European tree species or, if this is regarded as insufficient, assisted migration (i.e., the use of species suitable for the future climatic conditions) and, alternatively, substitution of native with non native species. The intraspecific (genetic and phenotypic) variability at a given site has been proven to be often higher than the variability among sites. Species with a large distribution range are supposed to have a wide variety of genotypes, allowing them to be adapted to different environmental conditions. Genetic variability and phenotypic plasticity are the key factors for the identification of useful tree genotypes for future forestation programs. Adaptation to drought, i.e., the probably most important future abiotic risk factor for forestry, can be reflected in variation of key functional traits (FT), at morphological, physiological and phenological level. FT utilized to screen for adapted genotypes in common gardens and provenance trials include growth, survival, leaf flushing and senescence, foliar features as leaf mass per area and nitrogen content, water use efficiency (e.g., estimated by analysis of the stable carbon isotopes, d13C) chlorophyll content, photosystem II functioning, and photosynthetic capacity under water shortage. Current modeled simulation of future forest distribution suggests the expansion of forests at the highest latitudes and altitudes, alongside with a reduction in the hottest and driest Mediterranean regions of South Europe. The general expectations, however, may be disproved especially at a regional level, by factors unexpected or not well known, such as possible extreme climatic events and increased roles of parasites/diseases (with negative effects), or high capacity of forest persistence or adaptation (with positive effects). Natural migration and species substitution can be hampered by co-factors of climate change, such as forest fragmentation and increased frequency and intensity of forest fires.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Adaptation; Extinction; functional traits; Local evolution; migration; Phenotypic plasticity; Phenotyping; provenances

Frost-acclimation of photosynthesis in overwintering Mediterranean holm oak, grown in Central Europe - Pflug, Ellen; Brüggemann, Wolfgang (International Journal of Plant Biology, 2012)
As a consequence of global change, forestry in Central Europe has to expect and be prepared for an increase of hot and dry summers in the near future. In two model plantations of the Mediterranean holm oak (Quercus ilex L.) in Central Europe (Rhine-Main basin) we tested its potential as a future forestry tree for drought-threatened stands by studying its overwintering strategy under harsh winter conditions. During prolonged frost periods, chronic photoinhibition was developed, which lasted until the end of the frost period. Nearly all plants survived minimum temperatures of - 16 to -18°C and their photosynthetic apparatus recovered completely during late winter. A detailed study of the temperature dependence of chlorophyll (chl) fluorescence parameters of the OJIP test revealed statistically significant correlations between minimum temperature and maximum quantum yield of primary photochemistry (Fv/Fm), absorption rate/reaction centre (ABS/RC), dissipation rate/reaction centre (DI0/RC) and electron transport rate/reaction centre (ET0/RC) as well as with the deepoxidation state (DES) of the xanthophyll pigments. The DES correlated with Fv/Fm, ABS/RC, DI0/RC and ET0/RC. It is concluded, that from the point of view of the winter hardiness of the photosynthetic apparatus, Q. ilex should be further investigated as a potential future forestry tree also for very dry and warm stands in Central Europe under the scenarios of climate change.
Keywords: chlorophyll fluorescence; ojip test; xanthophyll cycle

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions: II. Photoinhibitory and light-independent violaxanthin deepoxidation and downregulation of photosystem II in evergreen, winter-acclimated Euro - Brüggemann, Wolfgang; Bergmann, Michael; Nierbauer, Kai-Uwe; Pflug, Ellen; Schmidt, Carlo; Weber, Daniel (Trees, 2009)
In the context of the search for future forestry species in Central Europe under climate change scenarios, the evergreen Mediterranean Quercus taxa Q. ilex ssp. ilex and Q. suber and the semideciduous hybrids. Q. 9 turneri and Q. 9 hispanica were studied in relation to their photochemical efﬁciency of photosystem II and to the activity of the xanthophyll cycle under Central European winter conditions. The evergreen taxa were remarkably insensitive to winter stress in the ﬁeld and reacted towards frost periods with the phenomenon of ‘‘chronic photoinhibition’’, i.e. a decrease in pre-dawn Fv/Fm and an increase in the deepoxidation state of the xanthophylls. Under dark and warmer conditions (room temperature), winter-acclimated leaves of the evergreen taxa except for Q. 9 turneri produced zeaand antheraxanthin and decreased Fv/Fm, possibly by creation of a chlororespiratory pH-gradient. It is suggested that the ability for dark violaxanthin deepoxidation may contribute to the winter hardiness of the evergreen taxa.
Keywords: á downregulation of ps; chlororespiration; chlororespiration á photoinhibition á; downregulation of ps II; ii; photoinhibition; Quercus; quercus á winter acclimation; winter acclimation

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions: II. Photoinhibitory and light-independent violaxanthin deepoxidation and downregulation of photosystem II in evergreen, winter-acclimated Euro - Brüggemann, Wolfgang; Bergmann, Michael; Nierbauer, Kai-Uwe; Pflug, Ellen; Schmidt, Carlo; Weber, Daniel (Trees, 2009)
In the context of the search for future forestry species in Central Europe under climate change scenarios, the evergreen Mediterranean Quercus taxa Q. ilex ssp. ilex and Q. suber and the semideciduous hybrids. Q. 9 turneri and Q. 9 hispanica were studied in relation to their photochemical efﬁciency of photosystem II and to the activity of the xanthophyll cycle under Central European winter conditions. The evergreen taxa were remarkably insensitive to winter stress in the ﬁeld and reacted towards frost periods with the phenomenon of ‘‘chronic photoinhibition’’, i.e. a decrease in pre-dawn Fv/Fm and an increase in the deepoxidation state of the xanthophylls. Under dark and warmer conditions (room temperature), winter-acclimated leaves of the evergreen taxa except for Q. 9 turneri produced zeaand antheraxanthin and decreased Fv/Fm, possibly by creation of a chlororespiratory pH-gradient. It is suggested that the ability for dark violaxanthin deepoxidation may contribute to the winter hardiness of the evergreen taxa.
Keywords: á downregulation of ps; chlororespiration; chlororespiration á photoinhibition á; downregulation of ps II; ii; photoinhibition; Quercus; quercus á winter acclimation; winter acclimation